IMPLEMENTATION OF THE SMART VILLAGE CONCEPT BASED ON LOCAL WISDOM THROUGH THE EMPOWERMENT OF OFFICIALS AND THE COMMUNITY OF TABAH VILLAGE IN THE KKN PROGRAM - Alda; Rostiani, Winda; Aprilianti, Imelda; Chairulnisa; Try Lestari, Puspita; Nursafina; Ulfiyah Nabila, Andi; Sabir, Firnawati; Nurul Hidayah; Fatima, Siti; Asril Muslim, M.; Sabani, Akbar (International Journal of Multidisciplinary Reseach, 2025)
The Smart Village Community Service Program (KKN) based on local wisdom in Tabah Village aims to encourage village transformation towards more modern, inclusive, and digitally oriented governance. This activity uses the Asset-Based Community Development (ABCD) approach as the main strategy to map, optimize, and empower local assets, including human resources, economic potential, social institutions, and village digital infrastructure. The program implementation includes mapping village assets, digital literacy training, assistance in using the DIGIDES platform, creating village websites and social media accounts, and compiling maps and infographics of public services. The results of the activity show that the ABCD approach has succeeded in increasing the capacity of village officials in digital administration, expanding access to public information, and encouraging the active role of youth and the community in the digital transformation of the village. Although there are still obstacles in the form of limited internet access and digital literacy among some residents, high community participation and support from village officials are factors that support the sustainability of the program. Overall, this KKN activity proved that the integration of digital technology and local wisdom through the ABCD approach can be an effective model in the development of an independent and sustainable Smart Village.